EXCISE DUTY COMPLIANCE BEHAVIOR IN MALAYSIA - Zainol Bidin; Perabavathi Sinnasamy (International Journal of Accounting, Finance and Business, 2018)
Taxation became a main of revenue in most of the developed and developing countries. However, tax non-compliance remains a serious issue around the globe. The negative impact of tax non-compliance on the economy and the evolving nature of indirect tax in Malaysia have induced this study. Although this phenomenon always present, but less attention is given compared to direct taxes such as income and corporate taxes. Malaysian government was emphasizing on strengthening its financial capacities via indirect taxes. As a result, the establishment of raising indirect taxes revenue is needed to ensure a sustainable country’s development. However, the level of compliance among importers still not satisfied. Thus, the objective of this study is to examine the determinants of importers excise duty compliance. Using the deterrence theory as the basis of this study’s framework, data were collected from 500 useable excise duty offenders scattered throughout Malaysia. Results from regression analysis (partial least square) shown that penalty rate, the probability of detection and tax knowledge revealed a positive and significant relationship with excise duty compliance. Implications and recommendations for policy makers are discussed.